DEVELOPMENT OF CHANNEL PROCESSES AND MUDFLOWS ON MOUNTAIN RIVERS OF THE PRYKARPATTIA - Гнатів, Ігор; Гнатів, Роман (SWorldJournal, 2025)
Mudflows are a fairly common phenomenon in Ukraine and other countries of the world. In the Carpathian region of Ukraine, there are three mudslide-hazardous basins, which include the territories of Ivano-Frankivsk, Zakarpattia, Lviv and Chernivtsi regions